THE THERMAL STRUCTURE OF SUBDUCTION ZONE BACK ARCS - Currie C.A.; Hyndman R.D. (My University, 2006)
It is well recognized that active arc volcanism at nearly all subduction zones requires temperatures greater than 1200°C in the subarc mantle, despite the underthrusting cool subducting plate. In this study, we document evidence that high upper mantle temperatures are not restricted to the arc but usually extend for several hundred kilometers across the back arc, even in areas that have not undergone extension. For 10 circum-Pacific back arcs where there has been no significant recent extension, we have compiled observational constraints on the thermal structure using a number of independent indicators of mantle temperature, including surface heat flow, seismic velocity, and xenolith thermobarometry. The observations indicate uniformly high temperatures in the shallow mantle and a thin lithosphere (1200°C at ~60 km depth) over back-arc widths of 250 to >900 km. Similar high temperatures are inferred for extensional back arcs of the western Pacific and southern Europe, but the thermal structures are complicated by extension and spreading. A broad hot back are may be a fundamental characteristic of a subduction zone that places important constraints on back-arc mantle dynamics. In particular, the thermal structure predicted for slab-driven comer flow is inconsistent with the observed uniformly high back-arc temperatures. We favor the alternate model that heat is rapidly carried upward from depth by vigorous thermal convection in the back-arc upper mantle. Such convection may be promoted by low viscosities, resulting from hydration by fluids from the subducting plate. Following subduction termination, we find that the high temperatures decay over a timescale of about 300 Myr. Copyright 2006 by the American Geophysical Union.